CMLHS Eid Celebration - Yong, Ying Mei (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
30 August 2012. As Ramadhan came to an end and everybody was back from the long Eid holidays, the Staff Welfare Unit (UNIK) organized the CMLHS Eid Celebration, which was held on 30 August at the Banquet Hall, Chancellery.